2020
DOI: 10.2147/ott.s240775
|View full text |Cite
|
Sign up to set email alerts
|

<p>Durable Clinical Response of Advanced Lung Adenocarcinoma Harboring <em>EGFR-19del/T790M/BRAF<sup>V600E</sup></em> Mutations After Treating with Osimertinib and Dabrafenib Plus Trametinib: A Case Report</p>

Abstract: EGFR-T790M and BRAF V600E are the common resistance mechanisms to EGFRtyrosine kinase inhibitors (TKIs). Standard treatment for the triple mutations of EGFR-19del, T790M, and BRAF V600E is still under debate. Herein, we present a case of therapeutic efficacy of osimertinib and dabrafenib plus trametinib on a 63-year-old man with advanced lung adenocarcinoma. This patient reached a remarkable progression-free survival of 9 months without any serious adverse reaction. At the progression of the disease, C797S mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Several studies have revealed that the most frequent mechanisms underlying resistance to EGFR TKIs were the occurrence of EGFR gene mutations and SCLC transformation. 1,3,8 The patient in our case had EGFR ex19del before his initial treatment. However, EGFR exon20p.T790M point mutation, EGFR amplification, MYC amplification, RB1 exon 2 truncated mutations, and TP53 exon 5 frameshift mutations were detected after gefitinib treatment.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies have revealed that the most frequent mechanisms underlying resistance to EGFR TKIs were the occurrence of EGFR gene mutations and SCLC transformation. 1,3,8 The patient in our case had EGFR ex19del before his initial treatment. However, EGFR exon20p.T790M point mutation, EGFR amplification, MYC amplification, RB1 exon 2 truncated mutations, and TP53 exon 5 frameshift mutations were detected after gefitinib treatment.…”
Section: Discussionmentioning
confidence: 75%
“… 2 Targeted therapy inhibits the activity of epidermal growth factor receptor (EGFR) or other specific proteins known to be mutated. 3 However, most patients with NSCLC rapidly acquire drug resistance to EGFR tyrosine kinase inhibitors (TKIs). 4 The mechanisms of acquired drug resistance are complex and include the development of new gene mutations, transformation of NSCLC into SCLC, 5 and combination of NSCLC and SCLC histological subtypes at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all the patients who received brigatinib achieved a desirable efficacy. Another case report showed a patient who was treated by brigatinib and cetuximab progressed in only 1 month 18 . A retrospective study compared the clinical efficacy of brigatinib combination with cetuximab and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Another patient with advanced lung adenocarcinoma carrying EGFR -19del, T790M and B-RAF V600E mutations that received a similar three-drug combination treatment achieved a striking progression-free survival of 9 months and did not show any serious adverse reaction. 48 The same treatment regimen was also used to treat two NSCLC patients carrying EGFR 19del, T790M, and B-RAF V600E mutations in another case report, in which clinical response in one patient lasted for 13.4 months, but not in the other patient. 49 Similarly, the treatment of two cases of advanced NSCLC patients carrying EGFR 19del or L858R, T790M and B-RAF V600E mutations with osimertinib and the B-Raf V600E inhibitor, vemurafenib, combination achieved a noticeable improvement in clinical symptoms including physical mobility within 4 to 6 weeks from the initiation of the combination treatment.…”
Section: Introductionmentioning
confidence: 99%